2011
DOI: 10.4314/bcse.v25i3.68590
|View full text |Cite
|
Sign up to set email alerts
|

<b>Synthesis, characterization, antibacterial and antifungal studies of some transition and rare earth metal complexes of N-benzylidene-2-hydroxybenzohydrazide</b>

Abstract: The solid complexes of Cu(II), Co(II), Mn(II), La(III) and Ce(III) were prepared from bidentate Schiff base, N-benzylidene-2-hydroxybenzohydrazide. The Schiff base ligand was synthesized from 2hyhdroxybenzohydrazide and benzaldehyde. These metal complexes were characterized by molar conductivity, magnetic susceptibility, thermal analysis, X-ray diffraction, FTIR, 1 H-NMR, UV-Vis and mass spectroscopy. The analytical data of these metal complexes showed metal:ligand ratio of 1:2. The physico-chemical study supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The  eff values showed that the (2-8) and (10)(11)(12) complexes are paramagnetic. The Cu 2+ complexes (2)(3)(4)(5) show  eff values in the 1.70-1.75 BM range which are compatible with one unpaired electron Cu 2+ in octahedral environmental [24]. Ni 2+ complex (6) shows  eff value 2.85 BM which is compatible with two unpaired electrons system of octahedral Ni 2+ complex [42].…”
Section: Magnetic Momentmentioning
confidence: 72%
See 4 more Smart Citations
“…The  eff values showed that the (2-8) and (10)(11)(12) complexes are paramagnetic. The Cu 2+ complexes (2)(3)(4)(5) show  eff values in the 1.70-1.75 BM range which are compatible with one unpaired electron Cu 2+ in octahedral environmental [24]. Ni 2+ complex (6) shows  eff value 2.85 BM which is compatible with two unpaired electrons system of octahedral Ni 2+ complex [42].…”
Section: Magnetic Momentmentioning
confidence: 72%
“…Metal complexes, (3-4), (7)(8) and (10)(11)(12)(13) 2 with a suitable amount of a ligand ethanolic solution in molar ratio (1 metal : 2 ligand) in the presence of 2 mL of triethylamine. The reaction mixture was then refluxed for 3 hours.…”
Section: Metal Complexes Preparationmentioning
confidence: 99%
See 3 more Smart Citations